Resveratrol Inhibits Key Steps of Steroid Metabolism in a Human Estrogen-Receptor Positive Breast Cancer Model: Impact on Cellular Proliferation - Poschner, Stefan; Maier-Salamon, Alexandra; Zehl, Martin; Wackerlig, Judith; Dobusch, Daniel; Meshcheryakova, Anastasia; Mechtcheriakova, Diana; Thalhammer, Theresia; Pachmann, Bettina; Jäger, Walter (Frontiers in Pharmacology, 2018)
The role of resveratrol (RES) in preventing breast cancer is controversial, as low concentrations may stimulate the proliferation of estrogen-receptor alpha positive (ERα+) breast cancer cells. As metabolism is the key factor in altering cellular estrogens, thereby influencing breast tumor growth, we investigated the effects of RES on the formation of estrogen metabolites, namely 4-androstene-1,17-dione (AD), dehydroepiandrosterone (DHEA), dehydroepiandrosterone-3-O-sulfate (DHEA-S), estrone (E1), estrone-3-sulfate (E1-S), 17β-estradiol (E2), 17β-estradiol-3-O-(β-D-glucuronide) (E2-G), 17β-estradiol-3-O-sulfate (E2-S), 16α-hydroxy-17β-estradiol (estriol, E3) and testosterone (T) in ERα-MDA-MB-231 and ERα+ MCF-7 cells. Incubation of both of the cell lines with the hormone precursors DHEA and E1 revealed that sulfation and glucuronidation were preferred metabolic pathways for DHEA, E1 and E2 in MCF-7 cells, compared with in MDA-MB-231 cells, as the Vmax values were significantly higher (DHEA-S: 2873.0 ± 327.4 fmol/106 cells/h, E1-S: 30.4 ± 2.5 fmol/106 cells/h, E2-S: 24.7 ± 4.9 fmol/106 cells/h, E2-G: 7.29 ± 1.36 fmol/106 cells/h). RES therefore significantly inhibited DHEA-S, E1-S, E2-S and E2-G formation in MCF-7, but not in MDA-MB-231 cells (Kis: E2-S, 0.73 ± 0.07 µM < E1-S, 0.94 ± 0.03 µM < E2-G, 7.92 ± 0.24 µM < DHEA-S, 13.2 ± 0.2 µM). Suppression of these metabolites subsequently revealed 2-fold higher levels of active E2 concomitant with an almost 2-fold increase in MCF-7 cell proliferation, which was the most pronounced upon the addition of 5 µM RES.As the content of RES in food is relatively low, an increased risk of breast cancer progression in women is likely to only be observed following the continuous consumption of high-dose RES supplements. Further long-term human studies simultaneously monitoring free estrogens and their conjugates are therefore highly warranted to evaluate the efficacy and safety of RES supplementation, particularly in patients diagnosed with ERα+ breast cancer.